Knowledge and Practice Regarding Toilet Training among Mothers of Toddlers in Pokhara, Nepal - Poudel, Sabina; Lamichhane, Sabina (Asian Journal of Population Sciences, 2026)
Toilet training is an essential developmental milestone for toddlers and requires adequate knowledge and appropriate practice from mothers. Improper or delayed training may lead to anxiety, constipation, and behavioural problems in children. Despite its importance, limited evidence is available on mothers’ knowledge and practices related to toilet training in Nepal. This study aims to assess the level of knowledge and assess the practices regarding toilet training among mothers of toddlers in selected areas of Pokhara. A descriptive cross-sectional research design was used, non –non-probability purposive sampling technique was applied to select 178 mothers of toddlers. Data were collected through face-to-face structured interview questionnaires. Collected data was analysed using SPSS software with descriptive statistics (as frequency, percentage, mean and standard deviation) and inferential statistical tests as per the nature of the data. The study revealed that most (78.7%) of the participants had average knowledge, while 17.4% had poor knowledge, and only 3.9% demonstrated good knowledge regarding toilet training. The total mean knowledge score was 19.2 (SD=3.1). No significant association was found between the level of knowledge and selected socio-demographic variables. The study showed that the majority of mothers had an average level of knowledge regarding toilet training, with only a small proportion demonstrating good knowledge. No significant association was found between knowledge levels and socio-demographic variables. Although mothers possessed basic awareness, gaps remain in their understanding and application of appropriate toilet-training practices. Strengthening community-based health education and providing practical guidance to mothers can help enhance effective toilet-training practices and support healthy developmental outcomes in toddlers.